The Prevalence and Severity of Tooth Wear in Type 2 Diabetic Patients - Patcharawan Srisilapanan; Matee Jindarat; Jeffrey Roseman (International Journal of Dentistry)
Objective. To assess the prevalence and severity of tooth wear in type 2 diabetic patients. Methods. Attendees at a diabetic clinic at Wiang Pa Pao Hospital in Chiang Rai province, Thailand, were invited to take part in this cross-sectional study. All participants were aged 35–74 and had type 2 diabetes. Participants were required to have been diagnosed with diabetes for at least three months. 179 subjects accepted a clinical oral examination and completed the questionnaire. Tooth wear was assessed clinically using the Smith and Knight Tooth Wear Index. Results. The mean age of diabetic patients was 56.5 ± 7.8 years. The majority (44.1%) had diabetes more than 5 years. The average years of having had diabetes was 6.5 ± 6.3 years. The most prevalent type of tooth wear was attrition (99.4%). The prevalence of erosion, abrasion, and abfraction were 64.8%, 31.3%, and 7.3%, respectively. The majority of the tooth wear was moderate to high severity (62.1%). Erosion and abfraction showed significant association with age group (p<0.05). Age group was significantly associated with the severity level (p=0.017). Mild tooth wear severity was the highest in age groups 35–44 and 45–54 (53.8% and 41.2%, respectively). Moderate tooth wear was the highest proportion in age groups 55–65 and 65–74 (52.2% and 44.0%, respectively). There were no significant differences between specific diabetic symptoms and types of tooth wear. Conclusion. There was a high prevalence of tooth wear among diabetic patients. The role of prevention is vital in maintaining the integrity of the teeth and to avoid treating these worn teeth in diabetic patients.